2019
DOI: 10.3389/fnmol.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Knockout of Kcnip3 Enhances Pain Sensitivity and Exacerbates Negative Emotions in Rats

Abstract: The Ca2+-binding protein Kv channel interacting protein 3 (KChIP3) or downstream regulatory element antagonist modulator (DREAM), a member of the neuronal calcium sensor (NCS) family, shows remarkable multifunctional properties. It acts as a transcriptional repressor in the nucleus and a modulator of ion channels or receptors, such as Kv4, NMDA receptors and TRPV1 channels on the cytomembrane. Previous studies of Kcnip3-/- mice have indicated that KChIP3 facilitates pain hypersensitivity by repressing Pdyn exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
(49 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, Tian et al found that DREAM (N-terminal 31–50 fragment) interacts with transient receptor potential ion channel V1 (TRPV1) and exogeneous DREAM or N-terminal 31–50 fragment peptide alleviated CFA-induced thermal hyperalgesia behavior [ 65 ]. On the other hand, the genetic loss of DREAM in rats showed enhanced pain sensitivity in the CFA-induced pain model, along with increased anxiety/depression-like behavior [ 64 , 65 ]. Consistent with our findings, the alleviated morphine tolerance in melatonin-cotreated rats may be attributed to the increased Kcnip3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tian et al found that DREAM (N-terminal 31–50 fragment) interacts with transient receptor potential ion channel V1 (TRPV1) and exogeneous DREAM or N-terminal 31–50 fragment peptide alleviated CFA-induced thermal hyperalgesia behavior [ 65 ]. On the other hand, the genetic loss of DREAM in rats showed enhanced pain sensitivity in the CFA-induced pain model, along with increased anxiety/depression-like behavior [ 64 , 65 ]. Consistent with our findings, the alleviated morphine tolerance in melatonin-cotreated rats may be attributed to the increased Kcnip3 expression.…”
Section: Discussionmentioning
confidence: 99%
“… 31 The study by Le-Niculescu et al provided evidence for the involvement of NR4A2 gene in hippocampal anxiety. 32 Guo et al 6 evaluated pain sensitivity and negative emotional behavior in KCNIP3 -/- rats. It was confirmed that KCNIP3 -/- rats showed higher pain sensitivity, higher anxiety levels and aggravated depression-like behavior than wild-type rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it protects against inflammatory-mediated dopamine neuronal death. [5][6][7] The expression of NURR1 mRNA in adult mice was detected by in situ hybridization. After 30 min and 3 h of forced swimming experiment, the expression of NURR1 mRNA was increased not only in the whole cerebral cortex but also in the dopamine cell body region.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kcnip3, a DEG not identi ed as a hub gene, is a voltage-gated potassium channel gene. Its expression level decreased in the SNL group, which would reduce the potassium current causing neurons to remain in a high potential state for a longer time, thus promoting neuropathic pain [36].…”
Section: Discussionmentioning
confidence: 99%